VD_FINDINFO Pron / 2013 / 48 vom 28. Februar 2013 - VD Tribunal cantonal (2013)
CURATELLE, RECONSIDÉRATION, PROCÈS DEVENU SANS OBJET, ADOPTION, INTERNATIONAL | 450 CC, 450d al. 2 CC, 242 CPC (CH), 405 al. 1 CPC (CH), 17 LF-CLaH